Fast-track- recovery surgery with a wheyprotein-infused carbohydrate-loading drink pre-operatively and early oral feeding postoperatively among surgical gynaecological cancer patients: study protocol of an openlabelled, randomised controlled trial - Ho, Chiou Yi; Ibrahim, Zuriati; Abu Zaid, Zalina; Mat Daud, Zulfitri 'Azuan; Md Yusop, Nor Baizura (BioMed Central, 2020)
Introduction: There has been growing evidence on the favourable outcomes of fast-track-recovery (FTR) surgery; to expedite recovery, minimise complications, and reduce the length of hospital stay for surgical patients. However, there is lack of evidence on the effectiveness of FTR in surgical gynaecological cancer (GC) patients. Most of the previous studies did not focus on feeding composition in the FTR surgery protocol. This study aims to determine the effectiveness of FTR feeding with a whey-protein-infused carbohydrate-loading drink pre-operatively and early oral feeding post-operatively on post-operative outcomes among surgical GC patients. Methods/design: This open-labelled, randomised controlled trial (RCT) will randomly allocate patients into intervention and control groups. Ambulated Malaysian aged over 18 years and scheduled for elective surgery for (suspected) GC, will be included in this study. The intervention group will be given whey-protein-infused carbohydrate-loading drinks on the evening before their operation and 3 h before their operation as well as started on early oral feeding 4 h post-operatively. The control group will be fasted overnight pre-operation and only allowed plain water, and return to a normal diet is allowed when bowel sounds return post-operatively. The primary outcomes of study are length of post-operative hospital stay, length of clear-fluid tolerance, solid-food tolerance and bowel function. Additional outcome measures are changes in nutritional status, biochemical profile and functional status. Data will be analysed on an intention-to-treat basis.